Análisis del nivel de las barreras académicas y sociodemográficas en la eficiencia terminal de los estudiantes de la Facultad de Ciencias Sociales y Humanísticas - Torres Beltrán, José Andrés (2025)
Higher education in institutions such as ESPOL faces significant challenges, including ensuring that public investment is efficient. Among these challenges are academic and socioeconomic barriers that hinder students from completing their degrees within the expected timeframe. Therefore, this study analyzes the influence of academic and socioeconomic barriers on the academic performance of students in the Faculty of Social and Human Sciences and how transversal subjects impact student success. This study follows a quantitative approach with a non-experimental design, using data provided by the faculty, including grade records from 2017 to the first academic term of 2024, as well as a survey conducted with both active and graduate students. The results indicate that, on average, basic subjects are the main contributors to student attrition in the faculty. Additionally, as students' socioeconomic index increases, their likelihood of passing courses also increases. This trend is also observed in their probability of achieving higher academic averages. Keywords: eficiencia terminal, reprobación, deserción, expectativas salariales, éxito académico